Connecting boys with books 2 : closing the reading gap - Sullivan, Michael, 1967 August 30- (American Library Association, 2009)
Drawing on more than 20 years of experience, Sullivan shows how to reinvigorate the sense of excitement that boys felt when they first heard a picture book being read aloud.